Peran Tasawuf dalam Membangun Nilai Keagamaan Masyarakat Modern - Budi Handoyo (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2021)
The modern era is marked by advances in science and technology, which can bring prosperity to mankind. However, behind modern progress, there is a bad side that has greatly affected the inner side of Muslims. Modern negative impacts can be felt by the attitude of love for the world which gave birth to materialism and hedonism that occurs in various levels of society. The influence of technological sophistication, the sparkle of the world due to industrial progress and the development of western science that is rationalist, secularist, and materialistic have completely covered the eyes of the hearts of believers. walled in the eyes of the heart and mind in understanding the Divine Essence. The use of Sufism in this modern era is to improve our relationship with Allah and the Messenger, and our good relationship with fellow servants of Allah and His creatures. The main function of Sufism is to recognize the evils of passion. Because of this desire, it becomes the cause of various immoral actions such as ujub, arrogant, jealousy, angry and so on. To treat this liver disease, mental rehabilitation therapy is carried out in the form of spiritual education so that the heart can be clean from the impurities of lust and can know God.